Beyond the Blogosphere : Information and Its Children. - Barlow, Aaron, 1951- (ABC-CLIO, 2011)
This book looks at questions and answers pertaining to the organization, usage, and ownership of information in the Internet age--and the impact of shifting attitudes towards information ownership on creative endeavors.